Non-immunological determinants of transplanted kidney function longevity - Kolesnyk, M.; Stepanova, N.; Korol, L.; Shifris, I.; Zograbian, R.; Voronyak, O. (Ukrainian Journal of Nephrology and Dialysis, 2025)
Despite significant advancements in prolonging transplanted kidney function, its survival remains limited to approximately 10–12 years. Notably, the transplanted kidney function begins to decline progressively after the first post-transplantation year. The deterioration in graft function is driven by two primary categories of factors: immunologically mediated and non-immunologically mediated causes. Delayed graft function (DGF) serves as a quantitative and qualitative integrative manifestation of both immunological and non-immunological mechanisms, exerting a profound influence on both short-term and long-term transplant outcomes. The contribution of each factor is highly individualized for every recipient and fluctuates throughout the post-transplantation period. However, studies specifically addressing the non-immunological determinants of graft longevity, including the onset of DGF, remain scarce. This review systematizes key non-immunological determinants as potential therapeutic targets, which are crucial for timely intervention and the extension of transplanted kidney function. Maximizing graft longevity requires the identification of therapeutic targets and effective strategies to modulate both immunological and non-immunological factors in both the donor and the recipient. This analytical review aims to identify non-immunological determinants whose retrospective and prospective investigation may help establish therapeutic targets for prolonging transplanted kidney function.